2006
DOI: 10.4049/jimmunol.177.1.322
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TLR4 Polymorphic Variants: New Insights into TLR4/MD-2/CD14 Stoichiometry, Structure, and Signaling

Abstract: TLR4 is the signal-transducing receptor for structurally diverse microbial molecules such as bacterial LPS, respiratory syncytial virus fusion (F) protein, and chlamydial heat shock protein 60. Previous studies associated two polymorphic mutations in the extracellular domain of TLR4 (Asp299Gly and Thr399Ile) with decreased LPS responsiveness. To analyze the molecular basis for diminished responsiveness, site-specific mutations (singly or coexpressed) were introduced into untagged and epitope (Flag)-tagged wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
197
3
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(230 citation statements)
references
References 59 publications
25
197
3
5
Order By: Relevance
“…Both horse and human TLR4 show equal surface expression on HEK cells (2.16% horse TLR4 vs 1.29% human TLR4), but there are slight differences in the intracellular levels of TLR4 expression (7.28% for horse TLR4 vs 3.33% for human TLR4). These levels of TLR4 expression are comparable with those seen by others using similar transient transfection techniques (20).…”
Section: Constructssupporting
confidence: 89%
See 1 more Smart Citation
“…Both horse and human TLR4 show equal surface expression on HEK cells (2.16% horse TLR4 vs 1.29% human TLR4), but there are slight differences in the intracellular levels of TLR4 expression (7.28% for horse TLR4 vs 3.33% for human TLR4). These levels of TLR4 expression are comparable with those seen by others using similar transient transfection techniques (20).…”
Section: Constructssupporting
confidence: 89%
“…MD-2 binds to TLR4 on a lateral surface of the TLR4 solenoid near to the N terminus (18). Interestingly, TLR4 single nucleotide polymorphisms (D299G and T399I) in humans are located far away from the N-terminal MD-2 binding site but reduce LPS responsiveness (19,20). The mechanism for this is unclear, but the mutations could either affect the cooperative binding of LPS or alter the conformational changes that occur during ligand-induced signal transduction.…”
mentioning
confidence: 99%
“…5). Transfection studies show that these TLR4 variants do not exhibit a general defect in the transport of the receptor to the cell surface (39). Similarly, we have shown that the hyporesponsiveness to TLR1 agonists exhibited by the P315L variant is not due to lack of cell surface expression (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…38 These findings are supported by recent evidence that both TLR4 299Gly and TLR4 399Ile demonstrate decreased responsiveness to LPS and other TLR4 ligands in an in vitro reconstituted TLR4 signaling apparatus when compared to the TLR4 proteins bearing the major allele of each SNP (TLR4 Asp299 and TLR4 Thr399 ). 47 A construct containing both minor alleles had a significantly lower response to TLR4 stimulation than all other constructs, and all of these differences in responses were noted to be dependent on the stochiometry of TLR4, MD-2 and CD14. Thus, we have several clues that could implicate either or the combination of both minor alleles as being causal for susceptibility to IBD, but additional work is required to reconcile the results of these in vitro and ex vivo experiments and to confirm that no other polymorphism in this large TLR4 haplotype contributes to the susceptibility phenotype.…”
Section: Discussionmentioning
confidence: 94%